2016
DOI: 10.1103/physrevb.93.094416
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering studies of spin-phonon hybridization and superconducting spin gaps in the high-temperature superconductorLa2x(Sr,Ba)xCuO

Abstract: We present time-of-flight neutron-scattering measurements on single crystals of La2−xBaxCuO4 (LBCO) with 0 ≤x≤ 0.095 and La2−xSrxCuO4 (LSCO) with x = 0.08 and 0.11. This range of dopings spans much of the phase diagram relevant to high temperature cuprate superconductivity, ranging from insulating, three dimensional (3D) commensurate long range antiferromagnetic order, for x ≤ 0.02, to two dimensional (2D) incommensurate antiferromagnetism co-existing with superconductivity for x ≥ 0.05. Previous work on light… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
9
2
1
Order By: Relevance
“…There is also an enhancement of χ (ω) at ∼ 20 meV in the SC55 sample compared to the NSC sample. This feature appears to be similar to the one identified previously in lightly-doped La 2−x Ba x CuO 4 by Wagman et al [43], observed in other La-214 samples [19,22], and attributed to spin-phonon hybridization [65]. The apparent absence of such a feature in the NSC sample suggests that the coupling between spin-excitations and phonons requires a sufficient level of hole doping.…”
Section: Discussionsupporting
confidence: 88%
“…There is also an enhancement of χ (ω) at ∼ 20 meV in the SC55 sample compared to the NSC sample. This feature appears to be similar to the one identified previously in lightly-doped La 2−x Ba x CuO 4 by Wagman et al [43], observed in other La-214 samples [19,22], and attributed to spin-phonon hybridization [65]. The apparent absence of such a feature in the NSC sample suggests that the coupling between spin-excitations and phonons requires a sufficient level of hole doping.…”
Section: Discussionsupporting
confidence: 88%
“…They argued that the intensity enhancement was associated with a modification of the exchange coupling constant J using a vibration mode of Cu-O-Cu bond. A similar peak-structure was also reported for the UD region of LBCO and LSCO 21 . Motivated studies presented above, the purpose of this study is to gain insight into the relationship between intensity enhancement and superconductivity relating to spin excitations and clarifying the necessary conditions for intensity enhancement.…”
Section: Introductionsupporting
confidence: 85%
“…Our measurements also capture the antiferromagnetic spin waves. We check for a possible interaction between the spin waves and a low-energy optical mode of the type seen in Ba-and Sr-doped LCO [45,46], but find no evidence for such an interaction in the commensurate antiferromagnet, consistent with another recent neutron study [47].…”
Section: Introductionsupporting
confidence: 81%
“…In studies of antiferromagnetic spin fluctuations in La 2−x Ba x CuO 4 and La 2−x Sr x CuO 4 , Wagman et al [45,46] have identified evidence for spin-phonon coupling at energies in the range of 15-20 meV. We have observed a similar effect in our own samples of La 2−x Ba x CuO 4 [63] and La 2−x Sr x CuO 4 [64], and even in superconducting La 2−x Ca 1+x Cu 2 O 6 [65].…”
Section: Spin Fluctuationsmentioning
confidence: 99%